Towards eco-efficient lean production systems - Moreira, Francisco (2010)
Lean Production has proved itself a worthwhile production strategy in many distinct industries across all regions of the planet by achieving higher levels of production efficiency. Several authors identified that Lean inadvertently has had significant environmental gains. Such achievements are considered of special relevance in a global and highly competitive economy which is progressively both tied-up and driven by an environmental agenda. The main goal of the present study is to enlighten the contribution of Lean for achieving a better environmental performance of production systems and identify this as an emergent business model for supporting eco-efficiency.